Aurora B kinase erases monopolar microtubule-kinetochore arrays at the meiosis I-II transition - Sergio Villa-Consuegra; Víctor A. Tallada; Juan Jimenez (iScience, 2023)
Summary: During meiosis, faithful chromosome segregation requires monopolar spindle microtubule-kinetochore arrays in MI to segregate homologous chromosomes, but bipolar in MII to segregate sister chromatids. Using fission yeasts, we found that the universal Aurora B kinase localizes to kinetochores in metaphase I and in the mid-spindle during anaphase I, as in mitosis; but in the absence of an intervening S phase, the importin α Imp1 propitiates its release from the spindle midzone to re-localize at kinetochores during meiotic interkinesis. We show that “error-correction” activity of kinetochore re-localized Aurora B becomes essential to erase monopolar arrangements from anaphase I, a prerequisite to satisfy the spindle assembly checkpoint (SAC) and to generate proper bipolar arrays at the onset of MII. This microtubule-kinetochore resetting activity of Aurora B at the MI-MII transition is required to prevent chromosome missegregation in meiosis II, a type of error often associated with birth defects and infertility in humans.